Kendala Pada Pelayanan Pembuatan Izin Mendirikan Bangunan di Kabupaten Badung - I Nyoman Indra Kumara; I Nengah Riana; Komang Agus Ariana (Jurnal Ilmiah Telsinas, 2022)
On October 5, 2020 the Job Creation Act (UU Ciptaker) was passed and removed the requirements for a building permit (IMB) to obtain a development, structuring, and building construction permit. This is due to the complexity of the investment licensing process in Indonesia. Badung Regency is an attraction for investors to invest as well as apply for an IMB because it is a tourism area. This results in a lot of development and will indirectly increase the number of applications for IMB management. The process of obtaining IMB in Badung Regency is carried out by the Badung Regency Investment and One Stop Integrated Service (DPMPTSP). This study describes the constraints on the service of making IMB in Badung Regency. Collecting data using mixed research methods, quantitative descriptive analysis, and thematic analysis, in order to obtain 14 obstacles faced in IMB services in Badung Regency. These constraints can be grouped based on the processes that must be passed in the IMB service in Badung Regency. All of these obstacles were obtained based on literature studies, interviews with expert staff, as well as guided by regulations, time baselines, and criteria contained in the applicable SOPs.